Volterra Integral Equations by Variational Iteration Method - Danish Ul Islam; Dr. Anjali Shirivastava (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this research paper, numerical method Variational Iteration Method is used to solve Second Kind Volterra Integral Equation .Numerical examples illustrate the accuracy of the numerical method Variational Iteration Method.
Keywords: Fredholm Integral Equation; Variational Iteration Method; Fredholm Integral Equation of First Kind; Fredholm Integral Equation of Second Kind